Thiabowls: synthesis, molecular structure, and novel supramolecular architecture of trithia-[3]-peristylane - Mehta, Goverdhan; Gagliardini, Vanessa; Schaefer, Carsten; Gleiter, Rolf (Organic letters, 2004)
A synthesis of trithia-[3]-peristylane, C6H6S3, a novel C3v symmetric thiabowl, from the exotic hydrocarbon bullvalene has been accomplished. The X-ray crystal structure of this trithiabowl displays an unprecedented supramolecular architecture in the solid state with 12 CH···S interactions involving all of its six hydrogen atoms and the two lone pairs on each of the three sulfur atoms.